Caboodle of tricks

Calculus Level 5

0 x 4 ln ( x ) ( 1 + x 4 ) 2 d x \large \displaystyle \int_{0}^{\infty}{\frac{{x}^{4} \ln(x)}{{(1+{x}^{4})}^{2}}} \, dx

The above integral can be written as π a b c / d π e f g / h \displaystyle \frac{{\pi}^{a}}{{b}^{c/d}} - \frac{{\pi}^{e}}{{f}^{g/h}} for positive integers a , b , c , d , e , f , g , h a,b,c,d,e,f,g,h where b b and f f are prime numbers, with gcd ( c , d ) = gcd ( g , h ) = 1 \gcd(c,d) =\gcd(g,h) = 1 .

Give your answer as a + b + c + d + e + f + g + h \displaystyle a + b + c + d + e + f + g + h .

Details and Assumptions :

  • All of the letters need not represent distinct numbers.


The answer is 29.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sudeep Salgia
Jun 30, 2015

Let J J be the required integral. Consider the following integral with a parameter a a .
I ( a ) = 0 1 1 + x a d x I(a) = \int_0^{\infty} \frac{1}{1 + x^a} \text{ d}x I ( a ) = a 0 1 1 + x a d x = 0 x a ln ( x ) ( 1 + x a ) 2 d x = J \displaystyle \Rightarrow I'(a) = \frac{\partial }{\partial a} \int_0^{\infty} \frac{1}{1 + x^a} \text{ d}x = - \int_0^{\infty} \frac{x^a \ln (x) }{(1 + x^a)^2} \text{ d}x = - J .

So evaluating I ( a ) I(a) would be enough for evaluating J J . Infact I ( a ) I(a) is a standard integral of the form 0 x m 1 1 + x n d x \displaystyle \int_0^{\infty} \frac{x^{m-1}}{1 + x^n} \text{ d}x with m = 1 m = 1 and n = a n = a which evaluates to π n csc ( m π n ) \displaystyle \frac{\pi }{n} \csc \left(\frac{m \pi }{n} \right) .

So, I ( a ) = π a csc ( π a ) \displaystyle I(a) = \frac{\pi }{a} \csc \left(\frac{\pi }{a} \right) .

I ( a ) = csc ( π a ) cot ( π a ) π 2 a 3 csc ( π a ) π a 2 = J \displaystyle \therefore I'(a) = \csc \left(\frac{\pi }{a} \right) \cot \left(\frac{\pi }{a} \right) \frac{ \pi ^2 }{a^3} - \csc \left(\frac{\pi }{a} \right)\frac{\pi }{a^2} = -J .

Substitute a = 4 a=4 to get J = π 2 7 / 2 π 2 2 11 / 2 \displaystyle J = \frac{\pi }{2^{7/2}} - \frac{\pi^2 }{2^{11/2}} .

Compare the coefficients and add them up to get the final answer as 29 \boxed{29} .

For the standard integral:

I will prove the general form of

0 x m 1 1 + x n d x = π n sin m π n \int_0^\infty\frac{x^{m-1}}{1+x^n}\,dx=\frac{\pi}{n\sin\frac{m\pi}{n}}

It can easily be proven by taking substitution y = 1 1 + x n \displaystyle y=\frac{1}{1+x^n} and the integral becomes Beta function

1 n 0 1 y 1 m n 1 ( 1 y ) m n 1 d y = Γ ( 1 m n ) Γ ( m n ) n = π n sin m π n \frac{1}{n}\int_0^1 y^{\large 1-\frac{m}{n}-1}\ (1-y)^{\large \frac{m}{n}-1}\,dy=\frac{\Gamma\left(1-\frac{m}{n}\right)\Gamma\left(\frac{m}{n}\right)}{n}=\frac{\pi}{n\sin\frac{m\pi}{n}}

where the last part comes from Euler's reflection formula for the gamma function . Hence, by setting m = 1 m=1 , we have

0 1 1 + x n d x = π n sin ( π n ) = π n csc ( π n ) \int_0^\infty\frac{1}{1+x^n}\,dx=\frac{\pi}{n\sin\left(\frac{\pi}{n}\right)}=\frac{\pi}{n}\csc\left(\frac{\pi}{n}\right)

ι η τ ϵ g γ α τ ι ο η \iota \eta \tau \epsilon g \gamma \alpha \tau \iota \omicron \eta

@Kartik Sharma The wording of the problem has been updated for clarity.

Sudeep Salgia - 5 years, 11 months ago

Log in to reply

Thanks for that! I was going to edit the problem in the same way except the title. Nice! "Caboodle of tricks"-that quite suits the problem.

Oh and nice solution! I knew it could also be done using beta and Euler's reflection formula. I did it using contour integration/complex analysis. Will also post my approach but I don't think it's better than yours.

@Sudeep Salgia Thanks again for editing!

Kartik Sharma - 5 years, 11 months ago

Log in to reply

Thanks. No problem. I think the title was mostly given by Calvin Lin, so that credit should go to him.

Sudeep Salgia - 5 years, 11 months ago

Nice solution, Sir!

User 123 - 5 years, 11 months ago

same method! +1

Kazem Sepehrinia - 5 years, 11 months ago
Aditya Malusare
Dec 16, 2015

This solution uses contour integration.

We want to find the value of the integral ( R > 1 R > 1 ) J ( m ) = γ 1 1 + z m d z J(m) = \int_{\gamma} \dfrac{1}{1 + z^m} dz where γ \gamma is a sector in the complex plane, of radius R R and angle included from 0 to 2 π m \dfrac{2\pi}{m}

Divide the sector into 3 parts ( γ 1 , γ 2 , γ 3 ) \gamma_1, \gamma_2, \gamma_3) that correspond to the arc and the two lines that bound it. J ( m ) = γ 1 1 1 + z m d z + γ 2 1 1 + z m d z + γ 3 1 1 + z m d z J(m) = \int_{\gamma_1} \dfrac{1}{1 + z^m} dz + \int_{\gamma_2} \dfrac{1}{1 + z^m} dz + \int_{\gamma_3} \dfrac{1}{1 + z^m} dz Observe that for the arc \textbf{arc} (second part), the following argument holds. γ 2 1 1 + z m d z = γ 2 i R e i ϕ 1 + ( R e i ϕ ) m d ϕ \int_{\gamma_2} \dfrac{1}{1 + z^m} dz = \int_{\gamma_2} \dfrac{iR e^{i\phi}}{1 + (R e^{i\phi})^m} d\phi As R R \to \infty , the contribution of this integral γ 2 i R e i ϕ 1 + ( R e i ϕ ) m d ϕ 0 \int_{\gamma_2} \dfrac{iR e^{i\phi}}{1 + (R e^{i\phi})^m} d\phi \to 0

For the third part, parametrize z as z = x e 2 π i / m z = xe^{2\pi i/ m} , by which the integral becomes γ 3 1 1 + z m d z = R 0 e 2 π i / m 1 + x m ( e 2 π ) d x \int_{\gamma_3} \dfrac{1}{1 + z^m} dz = \int_{R}^{0} \dfrac{e^{2\pi i/m}}{1 + x^m(e^{2\pi})} dx

Hence, J ( m ) = γ 1 1 + z m d z = 0 1 1 + x m d x + 0 e 2 π i / m 1 + x m d x J(m) = \int_{\gamma} \dfrac{1}{1 + z^m} dz = \int_{0}^{\infty} \dfrac{1}{1 + x^m} dx + \int_{\infty}^{0} \dfrac{e^{2\pi i/m}}{1 + x^m} dx J ( m ) = ( 1 e 2 π i / m ) 0 1 1 + x m d x J(m) = (1 - e^{2\pi i / m})\int_{0}^{\infty} \dfrac{1}{1 + x^m} dx

By the method of residues, γ 1 1 + z m d z = 2 π i × Res { 1 1 + z m } z = e π i / m \int_{\gamma} \dfrac{1}{1 + z^m} dz = \left. 2\pi i \times \text{Res}\left\{ \dfrac{1}{1 + z^m}\right\} \right|_{z = e^{\pi i/m}}

Let z 0 = e π i / m z_0 = e^{\pi i/m} . The residue is equal to lim z z 0 ( z z 0 ) 1 1 + z m = lim z z 0 1 m z m 1 = z 0 m \lim_{z \to z_0} (z - z_0)\dfrac{1}{1 + z^m} = \lim_{z \to z_0} \dfrac{1}{m z^{m - 1}} = \dfrac{-z_0}{m} (Applying L'Hospital's Rule)

Hence, 0 1 1 + x m d x = 2 π i m e π i / m 1 e 2 π i / m \int_{0}^{\infty} \dfrac{1}{1 + x^m} dx = \dfrac{-2 \pi i}{m} \dfrac{e^{\pi i / m}}{1 - e^{2\pi i / m}}

Rearranging, we get 0 1 1 + x m d x = π m 1 sin ( π m ) = π m csc ( π m ) \int_{0}^{\infty} \dfrac{1}{1 + x^m} dx = \dfrac{\pi}{m} \dfrac{1}{\sin\left(\dfrac{\pi}{m}\right)} = \dfrac{\pi}{m}\csc\left(\dfrac{\pi}{m}\right)

Now, we know that 0 1 1 + x m d x = I ( m ) (say) = π m csc ( π m ) \int_{0}^{\infty} \dfrac{1}{1 + x^m} dx = I(m) \text{ (say)} = \dfrac{\pi}{m}\csc\left(\dfrac{\pi}{m}\right)

The required integral is I ( 4 ) -I'(4) which comes out to be I ( 4 ) = π 2 7 / 2 π 2 2 11 / 2 \displaystyle -I'(4) = \frac{\pi }{2^{7/2}} - \frac{\pi^2 }{2^{11/2}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...